The Applications and Mechanisms of Superoxide Dismutase in Medicine, Food, and Cosmetics - Zheng, Mengli; Liu, Yating; Zhang, Guanfeng; Yang, Zhikang; Xu, Weiwei; Chen, Qinghua (Antioxidants, 2023)
Superoxide dismutase (SOD) is a class of enzymes that restrict the biological oxidant cluster enzyme system in the body, which can effectively respond to cellular oxidative stress, lipid metabolism, inflammation, and oxidation. Published studies have shown that SOD enzymes (SODs) could maintain a dynamic balance between the production and scavenging of biological oxidants in the body and prevent the toxic effects of free radicals, and have been shown to be effective in anti-tumor, anti-radiation, and anti-aging studies. This research summarizes the types, biological functions, and regulatory mechanisms of SODs, as well as their applications in medicine, food production, and cosmetic production. SODs have proven to be a useful tool in fighting disease, and mimetics and conjugates that report SODs have been developed successively to improve the effectiveness of SODs. There are still obstacles to solving the membrane permeability of SODs and the persistence of enzyme action, which is still a hot spot and difficulty in mining the effect of SODs and promoting their application in the future.